Dopant-dependent thermoelectric performance of indoloindole-selenophene based conjugated polymer - Min Han, Ji; Eun Yoon, Sang; Hyun Jung, Ku; Bae, Onyu; Kim, Donguk; Kim, Unjeong; Seo, Hyungtak; Sunjoo Kim, Felix; Chul Kim, Ki; Kim, Jong H.; Kim, Bong Gi (Chemical Engineering Journal, 2022)
The development of organic conductors, which exhibit high electrical conductivity through chemical doping using non-acidic molecular dopants, has been challenging because of inefficient generation of free charge carriers. In this study, we synthesized a new conjugated polymer (CP) containing electron-donating indoloindole and biselenophene to devise an efficient doping platform. When the synthesized CPs were doped with electron acceptor (F4TCNQ) and Lewis acid (AuCl3) type dopants, both dopants realized high electrical conductivities (184 S·cm−1 for F4TCNQ and 283 S·cm−1 for AuCl3). Furthermore, the binding energies of the electron-donating atoms in the doped CPs and the degree of stabilization energy before/after doping indicated that Se and N atoms tended to interact more favorably with F4TCNQ and AuCl3, respectively. However, the Seebeck coefficient and power factor of the AuCl3-doped CP were lower than those of the F4TCNQ-doped CP, which was attributed to the larger amount of charge carriers generated by the AuCl3 dopant.
Keywords: Doping mechanism; Electron-donating; High electrical conductivity; Molecular dopant; Organic thermoelectric; Organics; Selenophene; Synthesised; Thermoelectric; Thermoelectric performance; Conjugated polymer; Doping mechanism; Molecular dopant; Organic conductor; Organic thermoelectrics